3106 The influence of early life experience on telomere length, health, and behavior of domestic cats - Delgado, Mikel Maria (J Clin Transl Sci, 2019)
OBJECTIVES/SPECIFIC AIMS: The primary objective of this research is to determine whether being hand-reared, and deprived of early maternal interaction, will affect telomere length in orphaned kittens. The secondary goal is to examine how early maternal separation impacts the health, growth and behavior of orphaned kittens. METHODS/STUDY POPULATION: Kittens were fostered through local rescue groups and shelters. We collected blood samples from 42 orphaned kittens during the first week of their lives. Due to high mortality of this population, we obtained a second blood sample at eight weeks of age from only 30 of these kittens. We collected blood samples from 12 control kittens raised with mothers at during the first and eighth weeks of life. Blood samples are currently being processed with real time quantitative PCR (qPCR) by the Real-time PCR Research and Diagnostics Core Facility at the UC Davis School of Veterinary Medicine (SVM). This includes RNA extraction, cDNA synthesis, Reference Gene Validation, and qPCR analysis. Relative telomere length (RTL) will be calculated by comparing the average telomere abundance across three samples cells with that of a reference gene (single copy number) for each sample. The resulting T/S ratio (telomere to single copy) is proportional to the average telomere length. If T/S = 1, then telomere length in the sample and the reference are the same. RESULTS/ANTICIPATED RESULTS: Because telomeres show the fastest rate of shortening early in life, we predict that maternal separation will increase the rate of telomere shortening in kittens. We also predict that the telomeres of orphaned kittens will be shorter at both one week and eight weeks of age, compared to controls. DISCUSSION/SIGNIFICANCE OF IMPACT: This study will increase our understanding of early life adversity, a finding that can translate to other mammals. It will inform the practice of fostering neonatal kittens, and illuminate whether these kittens might be at higher risk than mother-reared kittens for health problems (which could be investigated in future studies). If significant telomere shortening occurs between collection periods, then future studies can take more frequent blood samples to determine what stages of early development are potentially most sensitive. If differences between groups are found, this will establish a protocol for several future research projects, such as testing whether these detrimental effects can be mitigated by environmental enrichment via activation of telomerase. Telomerase is an enzyme that appears to counteract some shortening of telomeres, and is activated by several external factors, including exercise. Thus, a logical follow up study would be developing and testing age-specific and appropriate enrichments that may activate telomerase and reduce telomere loss. Physical contact, whether human, mother, or siblings, is another possible source of telomerase activation in young kittens. Future studies also could quantify the effects of different sources of physical contact on telomere shortening. Finally, a positive finding would establish a need for longitudinal studies of the effects of early weaning on feline health and behavior and whether differences in early-life telomere lengths predict health and longevity of cats.